Kebijakan Wisata Halal (Halal Tourism) Berbasis Kearifan Lokal di Kabupaten Lima Puluh Kota - Novianti Monyca; Muslim Muslim (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
This study examines the development of halal tourism based on local wisdom in Lima Puluh Kota Regency, focusing on the Harau Valley area as a leading destination. The research aims to analyze halal tourism development and identify challenges faced in its implementation. The study employs a descriptive qualitative approach with data collection techniques through in-depth interviews, field observations, and documentation studies. Research informants include the Department of Tourism, Youth and Sports, the Ministry of Religious Affairs, the Minangkabau Indigenous Leadership Council, Tourism Awareness Groups, business operators, and tourists. Data analysis uses the Miles and Huberman interactive model. The results show that halal tourism development in Harau Valley has great potential supported by natural compatibility with sharia principles, the philosophy of